2021
DOI: 10.3390/ijms22094434
|View full text |Cite
|
Sign up to set email alerts
|

Fabry Disease and the Heart: A Comprehensive Review

Abstract: Fabry disease (FD) is an X-linked lysosomal storage disorder caused by mutations of the GLA gene that result in a deficiency of the enzymatic activity of α-galactosidase A and consequent accumulation of glycosphingolipids in body fluids and lysosomes of the cells throughout the body. GB3 accumulation occurs in virtually all cardiac cells (cardiomyocytes, conduction system cells, fibroblasts, and endothelial and smooth muscle vascular cells), ultimately leading to ventricular hypertrophy and fibrosis, heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 213 publications
(415 reference statements)
1
25
0
2
Order By: Relevance
“…To our current knowledge, there are two clinical phenotypes of Fabry disease: classical and later-onset (non-classical) phenotypes. In the non-classical phenotype, renal, cardiac, and/or cerebrovascular manifestations are seen in adulthood [33]. Within the later-onset form, there is also a particular late-onset phenotype with a predominant cardiac variant, an intronic variant (IVS4 + 919G > C), common in Asian countries [23].…”
Section: Prevalence Of the Pulvinar Sign In Fabry Diseasementioning
confidence: 99%
“…To our current knowledge, there are two clinical phenotypes of Fabry disease: classical and later-onset (non-classical) phenotypes. In the non-classical phenotype, renal, cardiac, and/or cerebrovascular manifestations are seen in adulthood [33]. Within the later-onset form, there is also a particular late-onset phenotype with a predominant cardiac variant, an intronic variant (IVS4 + 919G > C), common in Asian countries [23].…”
Section: Prevalence Of the Pulvinar Sign In Fabry Diseasementioning
confidence: 99%
“…All the signs and symptoms in childhood and teenage years should raise the suspicion of FD and induce clinicians to perform an alpha-galactosidase enzymatic activity test on plasma or the blood pool, and confirm the diagnosis with a genetic test. Enzymatic replacement therapy (ERT) is an etiological therapy that blocks the progression of disease, often with a regression of LV hypertrophy and improvement of the prognosis of the patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…CMR techniques hold strong potential in AFD not only for guiding the appropriate timing for ERT introduction and prognostic classification, but also for monitoring response to therapy. For instance, several studies reported more effective results of ERT in terms of LV mass regression when little or no LGE was present at baseline evaluation [ 114 ] thus suggesting that specific treatment should be initiated earlier, as soon as the first structural or functional cardiac abnormalities become detectable and before development of myocardial fibrosis. Supplementary, material case 3 .…”
Section: Anderson Fabry Diseasementioning
confidence: 99%